The Dynamic Process Tracing Environment (DPTE) as a Tool for Studying Political Communication. (3rd April 2019) - Andersen, David J.; Redlawsk, David P.; Lau, Richard R.
Abstract : The dynamic process tracing environment (DPTE) is a unique and flexible tool permitting researchers to study information search and decision making in various manners. This article describes the rationale behind the system, some history of how it has revolutionized the study of voter decision making in elections, and some of the principles of design within the system.